Multiple Sclerosis: Perspectives in Treatment and Pathogenesis - Zagon, Ian S; McLaughlin, Patricia J (Exon Publications, 2017)
Multiple sclerosis is a chronic neurological disorder with devastating, long-term complications. MS is incurable, and most therapies treat only the symptoms leaving the patient with a reduced quality of life for extended periods of time. Most available therapeutic strategies target symptomatology, and not the pathophysiology of the disease. This book focuses on different biological pathways associated with MS and contains current information on the prevalence of multiple sclerosis, novel treatments that target pathophysiology, and new approaches for management of the disorder, as well as general knowledge about the disease process.